Edward III’s household knights in war and peace, 1327-1377 - Hefferan, Matthew (2018)
Over the last thirty years, Edward III has claimed his rightful place amongst the most successful kings of medieval England. A significant aspect of Edward’s reign that has as of yet been largely overlooked, however, is the place of the royal household knights within it. This is a significant omission for the household knights permeated many aspects of Edward’s reign and were integral to the way in which he conducted his wars and governed his kingdom.